Pengaruh Mindful Parenting dalam Menurunkan Stres Pengasuhan: Tinjauan Sistematik - Nazlah Hasni; Diah Karmiyati (Flourishing Journal, 2023)
Having children and becoming parents is the dream of most couples. Children are a gift, the apple of one's eye, a soulmate, and a source of hope. However, on the other hand, without denying the gratitude, it is undeniable that raising children is a significant task with all the complexities that follow. Without proper knowledge, the process of raising children can bring about pressure that can lead to stress. Certainly, this stress can have a negative impact on the well-being of parents and the growth of children. Mindful parenting is an awareness-based approach. Simply put, the main motivation of this approach is to enhance parents' abilities to fulfill their roles as primary caregivers and educators, both in terms of mind, emotions, and responses to their children. This systematic review aims to determine the influence of mindful parenting as an effective approach to dealing with parental stress in Indonesia. The method used is a literature review, where articles were obtained through the collection from the Publish and Perish 8 database of Google Scholar using inclusion and exclusion criteria. Keywords used in literature search include "mindful parenting," "parental stress," "happy parents," and "systematic review." The results indicate that out of the 16 scientific articles found, there is a significant influence between the implementation of mindful parenting and the reduction of parental stress levels. AbstrakMemiliki anak dan menjadi orang tua adalah impian sebagian besar pasangan. Anak adalah anugerah, buah hati, belahan jiwa, dan tumpuan harapan. Tapi di sisi lain, tanpa menafikan kesyukuran, tak dipungkiri jika mengasuh anak merupakan tugas besar dengan segala kompleksitas yang mengikuti. Bila tidak disertai ilmu yang baik, proses mengasuh putra-putri bisa saja mendatangkan tekanan yang dapat menciptakan stres. Tentu, stres ini akan berdampak negatif pada kesejahteraan orang tua dan tumbuh kembang anak. Mindful parenting adalah sebuah pendekatan berbasis kesadaran. Secara sederhana, motivasi utama pendekatan ini adalah untuk menaikkan kesanggupan orang tua dalam melakoni peran sebagai pengasuh dan pendidik utama, baik secara pikiran, emosi, dan respons terhadap buah hati. Tinjauan sistematik ini bertujuan untuk mengetahui pengaruh mindful parenting sebagai pendekatan yang efektif untuk mengatasi stres pengasuhan orang tua di Indonesia. Metode yang digunakan adalah systematic review yang mana artikel didapatkan dari pengumpulan melalui Publish and Perish 8 dari database Google Scholar dengan menggunakan kriteria inklusi dan eksklusi. Kata kunci yang digunakan dalam pencarian literatur: “mindful parenting”, “stress pengasuhan” “orang tua bahagia” dan “tinjauan sistematik”. Hasil menunjukkan bahwa dari 16 artikel ilmiah yang ditemukan menunjukkan adanya pengaruh yang signifikan antara penerapan mindful parenting terhadap penurunan tingkat stres pengasuhan.